EMIC Wave Properties Associated With and Without Injections in The Inner Magnetosphere. Issue 3 (30th March 2019) - Jun, C.‐W.; Yue, C.; Bortnik, J.; Lyons, L. R.; Nishimura, Y.; Kletzing, C.
Abstract: To understand the generation and propagation processes of electromagnetic ion cyclotron (EMIC) waves under different geomagnetic conditions in the inner magnetosphere, we performed a statistical study of EMIC wave properties observed by the Van Allen Probes from February 2013 to December 2016. We divided EMIC waves into two groups: those associated with and those occurring without injections observed by the Geostationary Operational Environmental Satellites (GOES‐13 and GOES‐15). We found that the EMIC wave polarization sense ε increased and the normalized frequency X decreased with increasing |MLAT|. Inside the plasmasphere, He + EMIC waves were predominantly observed with left‐hand polarization ( ε < −0.3) and higher wave normal angles ( θ k  = 30–40° ). Those associated with injections showed the most intense wave power at 14–16 MLT, compared to periods without injections when these waves exhibit a similar wave power but on the dayside. H + EMIC waves were predominantly observed outside the plasmasphere on the dayside and showed a mixture of left‐hand and linear polarizations ( ε  = −0.3–0.0) with lower wave normal angles ( θ k  = 20–30° ) regardless of injections. Moreover, H + EMIC waves were accompanied by a solar wind dynamic pressure enhancement (ΔPsw = 0.5 nPa). From these observations, we suggest that hot injected plasma contributes to the generation of intense He + EMIC waves in the afternoon sector. A mixture of expanding cold plasmaspheric ions and coexisting hot ring current ions acts as the free energy source for He + EMIC waves on the dayside during quiet times. Solar wind dynamic pressure enhancements are likely the major driver of H + EMIC waves outside the plasmasphere. Key Points: The spatial distributions of EMIC wave properties and |MLAT| dependence of polarization sense ε and normalized frequency X are examined Possible generation processes of EMIC waves under different environments in the inner magnetosphere are suggested He + EMIC waves inside the plasmasphere have left‐hand polarization while linear H + EMIC waves outside the plasmasphere are dominant